Contribution of Polish agrotechnical studies on Cannabis sativa L. to the global industrial hemp cultivation and processing economy - Poniatowska Joanna; Wielgus Karolina; Szalata Milena; Szalata Marlena; Ożarowski Marcin; Panasiewicz Katarzyna (Herba Polonica, 2019)
Industrial hemp (Cannabis sativa L.) attracts increasing interest of growers, in relation to both industrial and medical purposes. Construction is the most promising area of the economy for hemp, and specifically, the fast-growing production of insulation and bio-composite materials.